Representasi Perkawinan dalam Kristen di Era Modern - Yuwita Despriyantie (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines how Christian marriage is represented in the modern era through theological, symbolic, and contextual perspectives. Although Christian marriage is traditionally understood as a sacred covenant emphasizing unity, fidelity, and permanence, contemporary social realities reveal shifts in how Christians interpret and express marital life. Economic pressures, evolving family roles, digital communication patterns, and cultural influences shape the modern experience of marriage. Using a descriptive qualitative approach through literature-based research, this study analyzes the theological foundations, ritual symbols, and contextual factors that influence changes in the representation of Christian marriage today. The findings indicate that while the core theological essence of Christian marriage remains, its practical expressions undergo adaptation to remain relevant within modern life. Symbols such as wedding rings, marital vows, and liturgical blessings continue to convey theological meaning, while premarital education and pastoral support play a crucial role in strengthening marital stability. The study highlights the need for a contextual and integrative ecclesial approach that responds to the realities faced by Christian couples in contemporary society.